HUBUNGAN STATUS GIZI DENGAN LAMA PENYEMBUHAN LUKA POST SECTIO CESAREA - Peny Ariani; Putri Ayu Yessy Ariescha; Yulia Fahmila; Mutiara Dwi Yanti; Nurul Aini Siagian (Universitas Pahlawan Tuanku Tambusai, 2020)
The rate of cesarea section is not more than 15-20%. However, the data show that the rate of caesarea section in private hospitals in cities in Indonesia is above 30% and some even reach 80%. The aim of the study was to find out the relationship between nutritional status and the length of wound healing of sectio caesarea in public hospitals accompanied by Deli Tua in 2020. The method of the type of research used in this study is quantitative descriptive with the case control approach, using Purposive Sampling techniques. With a sample of 152 people. The research instrument used an IMT measuring instrument and observation sheet. The results T Independent test statistic were obtained P-value 0.000